2017
DOI: 10.1016/j.gore.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to cervical cancer treatment in Bangladesh: The development of a women's cancer ward at Dhaka Medical College Hospital

Abstract: Cervical cancer is the second most common cause of female cancer mortality worldwide. Concurrent chemoradiotherapy represents the standard of care for patients with stages IB2 to IVa cervical cancer. Unfortunately radiation therapy capacity is severely limited to non-existent in many Low and Middle-Income Countries. One solution has been to use chemotherapy to reduce tumor size to allow for radical surgery or in the case of inoperable cancers, as a placeholder until radiation is available. In Bangladesh, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…and lack of knowledge of cervical cancer risk factors. 15,[18][19][20] Other risk Infection with HPV spreads from one individual to another through sex, including vaginal, anal, and oral sex. In a recent study, the prevalence of HPV in both urban and rural women in Bangladesh was reported to be 7.7%.…”
Section: Risk Factors Associated With Cervical Cancer In Bangladeshmentioning
confidence: 99%
See 1 more Smart Citation
“…and lack of knowledge of cervical cancer risk factors. 15,[18][19][20] Other risk Infection with HPV spreads from one individual to another through sex, including vaginal, anal, and oral sex. In a recent study, the prevalence of HPV in both urban and rural women in Bangladesh was reported to be 7.7%.…”
Section: Risk Factors Associated With Cervical Cancer In Bangladeshmentioning
confidence: 99%
“…Chemoradiotherapy is the standard treatment for women with Stage IB2 to IVA disease; however, Bangladesh has a severe shortage of resources for radiation therapy. 19,38 For an individual with cervical cancer, the average waiting time for radiotherapy is 6 months. To reduce this long wait, Bangladesh has opted to provide neoadjuvant chemotherapy (NACT), 19 NACT before surgery.…”
Section: Current Treatments For Cervical Cancer In Bangladeshmentioning
confidence: 99%
“…Nevertheless, invasive examinations may cause adverse psychological effects, including anxiety, depression or distress (37). Surgery, chemotherapy and radiotherapy (38) are the three major therapeutic strategies in the treatment of CC; however, their uses may be limited for various reasons. Surgery may be limited by the status and stage of patients, including late stage or tolerance to anesthesia (39), whereas chemotherapy is limited due to the lack of sensitivity and the development of drug resistance (40).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with treatment barriers described in some LMIC ( Kivuti-Bitok et al, 2013 ; Makau-Barasa et al, 2017 ; Haque et al, 2017 ), NCI Paraguay had several strengths. The facility leadership and physicians were aware of the shortcomings of the treatment process and committed to improving it.…”
Section: Discussionmentioning
confidence: 99%